MRI evaluation of sacral chordoma treated with carbon ion radiotherapy alone. Issue 2 (August 2018) - Preda, Lorenzo; Stoppa, Davide; Fiore, Maria Rosaria; Fontana, Giulia; Camisa, Sofia; Sacchi, Roberto; Ghitti, Michele; Viselner, Gisela; Fossati, Piero; Valvo, Francesca; Vitolo, Viviana; Bonora, Maria; et al.
Abstract: Background and purpose: To compare RECIST 1.1 with volume modifications in patients with sacral chordoma not suitable for surgery treated with carbon ions radiotherapy (CIRT) alone. To evaluate patients pain before and after CIRT. To detect if baseline Apparent Diffusion Coefficient values (ADC) from Diffusion Weighted sequences could predict response to treatment. Material and methods: Patients included had one cycle of CIRT and underwent MRI before and after treatment. For each MRI, lesion maximum diameter and volume were obtained, and ADC values were analyzed within the whole lesion volume. Patients pain was evaluated with Numerical Rating Scale (NRS), considering the upper tumor level at baseline MRIs. Results: 39 patients were studied (mean follow-up 18 months). Considering RECIST 1.1 there was not a significant reduction in tumor diameters ( p  = 0.19), instead there was a significant reduction in tumor volume ( p  < 0.001), with a significant reduction in pain ( p  = 0.021) if the tumors were above vertebrae S2–S3 at baseline MRIs. The assessment of baseline ADC maps demonstrated higher median values and more negative skewness values in progressive disease (PD) patients versus both partial response (PR) and stable disease (SD). Conclusions: Lesion volume measurement is more accurate than maximum diameter to better stratify the response of sacral chordoma treated with CIRT. Preliminary results suggest that baseline ADC values could be predictive of response to CIRT.